2014
DOI: 10.1155/2014/983781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Autoimmune Profile of Scleroderma Patients from Western India

Abstract: Background. Systemic sclerosis (SSc, scleroderma) is a disorder characterized by fibrosis of skin and visceral organs. Pathogenesis of scleroderma is complex and is incompletely understood as yet. Autoantibodies in SSc represent a serologic hallmark which have clinical relevance, with diagnostic and prognostic potential. Objectives. To study distribution of clinical manifestations and to identify frequency of autoantibodies among subtypes of scleroderma patients from Western India. Methodology. One hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
6
21
0
Order By: Relevance
“…Such a high frequency of Raynaud's phenomenon has been similarly reported in other cohorts, e.g., in 97.3% of Egyptian patients, 95% of Iranian patients, and 76.5% of Indian patients. 15–17…”
Section: Discussionmentioning
confidence: 99%
“…Such a high frequency of Raynaud's phenomenon has been similarly reported in other cohorts, e.g., in 97.3% of Egyptian patients, 95% of Iranian patients, and 76.5% of Indian patients. 15–17…”
Section: Discussionmentioning
confidence: 99%
“…Detection of SSc-speci c ANAs is not only bene cial for diagnosis but is also clinically useful for classifying SSc subtypes that are exclusively associated with characteristic clinical phenotypes [11]. According to the study of Cristinane et al on an African-Brazilian population [12], anti-Scl-70 was present in 38.1% of patients with dcSSc and 25.0% of patients with lcSSc; in another cohort study, ACA was present in 9% of dcSSc patients and 38% of lcSSc patients [3]. Bardoni and colleagues [13] indicated that 7.8% of SSc patients had anti-RNP III antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of anti-Scl-70 antibodies is a marker of more extensive skin brosis and clinically signi cant pulmonary brosis, which predicts a poor prognosis. Conversely, anti-centromere antibodies are typically associated with localized cutaneous systemic sclerosis (lcSSc), infrequent lung, heart and kidney involvement, and late onset of pulmonary arterial hypertension (PAH), representing an overall good prognosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…25 This finding is also likely true for other regions where the distribution between lcSSc and dcSSc and autoantibodies may be different from North America and Europe. [26][27][28][29][30][31] Abbreviations: 1, positive; Ab, antibody; ANA, antinuclear antibody; ILD, interstitial lung disease; PAH, pulmonary arterial hypertension; WBC, white blood cell count. a A score of 9 or more is necessary to classify SSc.…”
Section: Classification Of Systemic Sclerosismentioning
confidence: 99%